2003
DOI: 10.1086/378900
|View full text |Cite
|
Sign up to set email alerts
|

“Are We There Yet?”: Deciding When One Has Demonstrated Specific Genetic Causation in Complex Diseases and Quantitative Traits

Abstract: Although mathematical relationships can be proven by deductive logic, biological relationships can only be inferred from empirical observations. This is a distinct disadvantage for those of us who strive to identify the genes involved in complex diseases and quantitative traits. If causation cannot be proven, however, what does constitute sufficient evidence for causation? The philosopher Karl Popper said, "Our belief in a hypothesis can have no stronger basis than our repeated unsuccessful critical attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 64 publications
0
121
0
3
Order By: Relevance
“…When the data for both sexes were combined, the haplotype frequency in patients (5.2%) was significantly higher than that in controls (3.5%) (OR 1.53, 95% CI 1.02-2. 30). An analysis of pairwise linkage disequilibrium between ASPN 5-SNP haplotypes and the ASPN aspartic acid repeat alleles revealed that specific SNP haplotypes were commonly associated with the 3 most common aspartic acid repeat alleles (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the data for both sexes were combined, the haplotype frequency in patients (5.2%) was significantly higher than that in controls (3.5%) (OR 1.53, 95% CI 1.02-2. 30). An analysis of pairwise linkage disequilibrium between ASPN 5-SNP haplotypes and the ASPN aspartic acid repeat alleles revealed that specific SNP haplotypes were commonly associated with the 3 most common aspartic acid repeat alleles (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The strongest evidence for a real connection between a gene and a disease or trait should come from a systematic replication of a statistically significant association, in which any source of bias or inconsistency has been eliminated (30). After several independent groups of investigators replicate a finding, it seems reasonable to conclude with sufficient certainty that a link between a gene and a disease has been demonstrated (31).…”
mentioning
confidence: 99%
“…51 Attempts to combat this problem often focus on P-values, with the rationale that by choosing the models least likely to be found by random chance alone, the probability of including a false positive will be greatly reduced. 52 Unfortunately, when considering a complex trait, the effect sizes of individual SNPs and pairwise interactions are generally fairly small. This limits the significance level that these models are able to attain in typical epidemiologic studies, which means that true positives may be removed during P-value adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…A major impediment in studying the contribution of genetic variation to interindividual variation in quantitative levels of apolipoproteins, and other risk factors for developing coronary heart disease, is that the available statistical models are not realistic representations of the biological complexity of genotype-phenotype relationships (Page et al 2003;Sing et al 2003). Phe-nomena such as allelic and genotypic heterogeneity, pleiotropy, gene by environment interaction and gene by gene interaction (epistasis) are realities that cannot easily be modelled, or estimated and tested, using population based samples of human data (Clark, 2000).…”
Section: Introductionmentioning
confidence: 99%